Microbiological surveillance of operation theatre in a tertiary care hospital in North East India - Yadav, Monika; Pal, Rohan; Sharma, Somorjit H.; Khumanthem, Sulochana D. (International Journal of Research in Medical Sciences, 2017)
Background: Good hospital hygiene is an integral part of infection control programme. “Microbiological surveillance” provides data about the factors contributing to infection. Bacterial counts in operation theatres are influenced by number of individual present, ventilation and air flow methods. Purpose of the study is to find out prevalence rate of microorganisms in Operation Theatre, to find out the frequency of contamination from various sites in operation theatre. Methods: The study was conducted in the department of microbiology, Regional institute of medical sciences, Imphal, Manipur, India. Air samples were taken by settle plate method in petri dishes containing blood agar and surface samples were taken by a sterile swab soaked in nutrient broth from all operation theatres. The samples were processed according to standard operative procedures. Results: Least bacterial colony forming unit (CFU) was shown by ophthalmology OT 17 CFU/mm3 and highest was shown by emergency OT 200 CFU/mm3. Isolated organism was divided into normal flora (CONS, micrococci), contaminant (bacillus species) and pathogenic organism e.g. Staphylococcus aureus, Acinetobacter spp., Pseudomonas spp. 15 (23.4%) swab samples out of a total of 64 swab samples were found to be growth positive. Out of that 4 CONS, 4 micrococci, 3 Bacillus spp, 2 Acinetobacter spp, 1 Enterobacter spp, 1 Pseudomonas spp. were isolated. Conclusions: Strengthening surveillance and laboratory capacity will surely enhance infection prevention and control. Routine sampling is strongly recommended for increasing awareness to identify and control all possible sources and types of infections.